Model for prediction of the optimal dose of Jatropha curcas in FS dewatering. Issue 11 (3rd November 2022) - Benjamin, Doglas Mmasi; Kimwaga, Richard
Abstract: Jatropha curcas (JC) is a highly effective conditioner in dewatering fecal sludge (FS); however, there are limited studies on the model predicting its optimal dose. This study presents the results of the developed model for predicting JC optimal doses. The developed model assessed the FS parameters and JC stock solution. We analyzed the FS samples from a mixture of a pit latrine and septic tank at the water quality laboratory of the University of Dar es Salaam. The multiple linear regression model was used to establish a relationship between JC optimal dose as a function of FS characteristics (pH, electrical conductivity, total solids, total suspended solids and concentration of the JC stock solution). The results indicated that 90.4% of the JC optimum dosage was determined and contributed by FS characteristics and JC stock solution concentrations. Also, the main explanatory factors determining the JC optimal dose were the JC stock solution concentration, followed by the pH of FS. The model results showed a good agreement between the predicted and observed JC optimal dose with a coefficient of determination of R 2 = 0.904 and 0.7879 for calibration and validation, respectively. Therefore, the model can be adapted to determine the JC optimal dose without running the jar test experiment. HIGHLIGHTS: Effects of physical–chemical characteristics of fecal sludge on Jatropha curcas dose. Physical–chemical predictor of fecal sludge on dewaterability. Concentration of J. curcas solution on the optimal dose of J. curcas . J. curcas optimal dose model. J. curcas optimal modal validation.